Paralympic versus Olympic canoe sprint: Comprehension of the development trajectory of the kayak 200 meters - Ribeiro Neto, F.; dos Santos, L. G. T. F.; Castelli Correia de Campos, L. F.; Winckler, C.; Gomes Costa, R. R. (Perceptual and Motor Skills, 2024)
Improvements in race times for male and female Para canoe athletes across different sports classes have led to a reduction in relative differences between classes over time. However, there is a lack of research examining the comparative developmental trajectories between high-performance Paralympic (PCS) and Olympic (OCS) canoe sprint. In this study, we compared the developmental trajectories of 200-meter kayak performances among PCS and OCS athletes. In total, we analyzed 628 race results obtained from public online databases, for nine competitions between 2015 and 2023. Race times were reduced over the years except in specific sports classes (KL3-M, K1-M, and K1-F; KL: Kayak Level, M: male, F: female), with a poor positive correlation (r = 0.17 to 0.33) between time and the years. For the remaining sports classes, these correlations ranged from poor to fair (r = -0.58 to -0.13). OCS K1 athletes outperformed their Paralympic counterparts. Among Paralympic classes, KL1 had slower times than KL2 and KL3 (p = .05), with KL2 times significantly lower than KL3 in the female category. OCS athletes exhibited less variability in race times compared to PCS athletes. In the male category, there were no significant differences in the coefficients of variation (CV) and amplitude of race times between sport classes, except for KL1-M, which had a larger CV than K1 (p = .05). In the female category, the CV and amplitude of race times were significantly higher in KL1-F compared to KL3-F and K1-F. OCS times remained stable from 2015, with KL3-M following a similar trend. PCS displayed greater race time variability, particularly in higher impairment classes, notably KL1. This underscores the existence of distinct developmental stages within the canoe sprint modality, particularly emphasizing the early developmental phase of KL1. It also provides valuable insights for coaches and sports selection, especially concerning athletes with more severe impairments, including those in Rehabilitation Centers and during athlete recruitment.